American global strategy and the 'war on terrorism" - Gardner, Hall (Ashgate, 2005)
Following the success of the original hardback publication, this revised and updated paperback re-conceptualizes the 'war on terrorism' and analyzes the nature of American domestic and international policy-making within the context of historical and structural constraints upon US policy.